The Managing Hotel Employees Achieving Wow!: A Conceptual Paper - Hastjarjo, Kelik (E-Journal of Tourism, 2023)
Managing Hotel Employees Achieving Wow! is a conceptual model. The process starts when employees have to serve customers with the best culture for customers. If customers start off on the right foot. It is an experience where customers feel the pleasure of interacting with employees. By linking each activity category together into a simpler system, this model creates many opportunities to repeat the cycle through customer satisfaction and loyalty.   Keywords : hospitality culture, hospitality people, hospitality service cycle